2017
DOI: 10.3389/fphar.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Osteosarcoma, Chondrosarcoma, and Ewing Sarcoma

Abstract: Osteosarcoma is the most frequent malignant bone neoplasm, followed by chondrosarcoma and Ewing sarcoma. The diagnosis of bone neoplasms is generally made through histological evaluation of a biopsy. Clinical and radiological features are also important in aiding diagnosis and to complete the staging of bone cancer. In addition to these, there are several non-specific serological or specific molecular markers for bone neoplasms. In bone tumors, molecular markers increase the accuracy of the diagnosis and assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 114 publications
(171 reference statements)
1
89
0
Order By: Relevance
“…So as to improve the overall survival rate of OS patients, a better understanding of the underlying molecular mechanism of OS is needed. Previous studied have demonstrated several target biomarkers of OS based on both gene expression pro ling and micro-RNA pro ling of the primary tumor [21]. Wang and Baumhoer et al had analyzed the OS sample by RT-PCR or immunohistochemistry and observed that insulin-like growth factor-1 receptor (IGF-1R) and cysteine-rich intestinal protein 1(CRIP1) were independent prognostic markers for OS and the high expression of these two markers was correlated with progression and metastasis of OS [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…So as to improve the overall survival rate of OS patients, a better understanding of the underlying molecular mechanism of OS is needed. Previous studied have demonstrated several target biomarkers of OS based on both gene expression pro ling and micro-RNA pro ling of the primary tumor [21]. Wang and Baumhoer et al had analyzed the OS sample by RT-PCR or immunohistochemistry and observed that insulin-like growth factor-1 receptor (IGF-1R) and cysteine-rich intestinal protein 1(CRIP1) were independent prognostic markers for OS and the high expression of these two markers was correlated with progression and metastasis of OS [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…[44] These results suggest that miR-145-3p may play a role as a tumor suppressor in OSs. [45,46] Circular RNAs(circRNAs) have a circular structure and represent a common class of the uncoded RNAs. Many circRNAs have been reported to play a significant role in cancer development and to have the potential to serve as a new bioindicator class for clinical diagnosis.…”
Section: Mirna Circrna and Lncrna In Osteosarcomamentioning
confidence: 99%
“…Osteosarcoma (OS) is a primary malignant bone tumor that has bimodal age distribution with the first peak of invasion occurs on children and adolescence between the ages of 10 and 20 years old, and the second peak of invasion occurs after 65 years of age [1]. Although OS incidences are rare, OS has been reported as the most common primary malignant bone tumor (36%) followed by chondrosarcoma (20-25%) and Ewing sarcoma (16%) [2,3] and it has been pre-dominated by male with the ratio of 1.6-1.7:1 [4]. To date, the current therapeutic strategies are still unable to provide promising long-term OS prognosis, whereby over 40% of patients experience relapsed and 20% of patients were diagnosed with metastatic OS [5].…”
Section: Introductionmentioning
confidence: 99%